Human Suffering and Theological Construction of Suffering - Sonny Eli Zaluchu (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
Suffering, as a natural part of life, will be burdensome and burdensome when we respond in the wrong way. Therefore, it is necessary to have a theological construction so that humans can survive and pass through their sufferings victoriously. This paper aims to build a theological response to human suffering by proposing the presence of a theology of suffering. It can be concluded that through the theology of suffering, suffering humans can accept suffering as God's sovereignty. This theology also builds on the understanding that the way of suffering can identify God. The suffering experienced by humans does not come immediately because it has a unique purpose for everyone. It is also found that in the theology of suffering, God suffered through the death of His Son on the Cross for the benefit of humanity. This paper is written entirely with an analytic approach by relying on various theories and interpretations of Bible verses through in-depth literature studies ABSTRAK: Penderitaan sebagai bagian alami kehidupan, akan menjadi sesesuatu yang membebani dan menjerumuskan ketika ditanggapi dengan cara yang salah. Oleh sebab itu, diperlukan kehadiran sebuah konstuksi teologis agar manusia dapat bertahan dan melewati penderitaanya dengan kemenangan. Paper ini bertujuan untuk membangun tanggap teologis terhadap penderitaan manusia dengan mengusulkan kehadiran teologi penderitaan. Disimpulkan bahwa melalui teologi penderitaan, manusia yang menderita dapat menerima penderitaan sebagai sebuah kedaulatan Tuhan. Teologi ini juga membangun pengertian bahwa Allah dapat dikenali melalui jalan penderitaan. Penderitaan yang dialami manusia tidak hadir serta merta karena memiliki tujuan khas bagi setiap orang. Juga ditemukan bahwa di dalam sebuah teologi penderitaan, Allah ikut menderita melalui kematian anak-Nya di atas Salib untuk kepentingan manusia. Paper ini sepenuhnya ditulis dengan pendekatan analitik dengan mengandalkan berbagai teori dan tafsiran ayat-ayat Alkitab melalui pendalaman kajian pustaka.